National Registry of Patients with Chronic Kidney Disease and Patients with Acute Kidney Injury 20 years: acquisitions and perspectives - M. Kolesnyk; N. Kozliuk; O. Razvazhaeva (Ukrainian Journal of Nephrology and Dialysis, 2022)
The history of the establishment of the National Registry is rather complicated and proceeds in several stages. It started in 2002, and the multistage nature of the Registry is related to the medical and technological changes that ensure the functioning of the registry (modification of the individual registration forms and the reporting form), as well as to the target groups of patients (patients with chronic kidney disease, kidney transplant recipients, or patients with acute kidney injury).The National Registry is managed by its coordinating committee, and regional registries are managed by regional coordinators. The rating evaluation of the status of medical care of nephrology patients in Ukrainian regions and Kyiv is prepared annually based on the regional registries.We believe that the transformation of the effective aggregated version of the Registry into an online version is necessary and perspective.